• The Effect of Public Sector on Private Jobs: Evidence from Palestine - Fallah, Belal (Journal of Economic Systems, 2021)
This paper estimates the short run effect of creating more public jobs on private employment in the occupied West Bank. Unlike most cited research, the results provide evidence that favors crowd-in effect both at the aggregate employment level and across sectors. A main contribution of the paper is to empirically explore the underlying mechanisms that drive the results. They include positive public employment effect on local demand, lack of public wage premium, as well as no effect on private wages. It turns out that an increase in the local labor force participation is a driving factor for the latter channel. Interestingly, the increase in labor force participation exceeds that of public and private employment, leading to an increase in the number of job seekers.
Keywords: Public employmentLabor demandCrowd-In effectExcess labor supply